2016
DOI: 10.1089/aid.2015.0336
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chloroquine on Immune Activation and Interferon Signatures Associated with HIV-1

Abstract: Immune activation associated with HIV-1 infection contributes to morbidity and mortality. We studied whether chloroquine, through Toll-like receptor (TLR) antagonist properties, could reduce immune activation thought to be driven by TLR ligands, such as gut-derived bacterial elements and HIV-1 RNAs. AIDS Clinical Trials Group A5258 was a randomized, double-blind, placebo-controlled study in 33 HIV-1-infected participants off antiretroviral therapy (ART) and 37 participants on ART. Study participants in each co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…It was a randomized, double-blind, placebo-controlled study in 33 HIV-1-infected participants off antiretroviral therapy and 37 participants on antiretroviral therapy. CQ modestly reduced immune activation in antiretroviral therapy-treated HIV-infected participants [42].…”
Section: Chloroquine and Hydroxychloroquine And Hivmentioning
confidence: 98%
See 1 more Smart Citation
“…It was a randomized, double-blind, placebo-controlled study in 33 HIV-1-infected participants off antiretroviral therapy and 37 participants on antiretroviral therapy. CQ modestly reduced immune activation in antiretroviral therapy-treated HIV-infected participants [42].…”
Section: Chloroquine and Hydroxychloroquine And Hivmentioning
confidence: 98%
“…Increased HIV-1 replication and decreased CD4 numbers [41] Chloroquine NCT00819390 Modest reduction in immune activation [42] Chloroquine NCT02004314…”
Section: Artesunate and Hcmvmentioning
confidence: 99%
“…In some studies this molecule was shown to reduce immune activation markers (i.e., IL-6, TNF-a and LPS) and CD8 T-cells expressing CD38CHLA-DRC and Ki-67, 158-161 while other researchers found no effect on immune-activation. [162][163][164] A possible target is also represented by TNF itself, which may be antagonized by several molecules currently in use for rheumatologic diseases. A study in rhesus macaques showed that adalimumab, a human anti-TNF monoclonal antibody, was able to reduce infiltration of polymorphonuclear cells into the T-cell zone of lymphoid tissues, diminishing also lymphoid tissue fibrosis; nevertheless, no effect on plasma immune activation was proven.…”
Section: New Treatment Strategies and Immunotherapy In Aging Hiv Patimentioning
confidence: 99%
“…Out of 92 studies included, eight were on COVID-19 [21][22][23][24][25][26][27][28], 13 studies were on malaria [29][30][31][32][33][34][35][36][37][38][39][40][41], 11 on other infectious conditions [42][43][44][45][46][47][48][49][50][51][52][53], 31 were on rheumatology , four on dermatologic diseases [85][86][87][88], eight on cancer [89][90][91][92][93][94][95][96], ve were on metabolic disease [97][98][99][100][101],...…”
Section: Study Characteristicsmentioning
confidence: 99%